The Effect of Discovery Learning Model on Students' Learning Outcomes on the Protists Concept - Dyamayanti, Lia; Fatimah, Shaynen; Lestari, Iing Dwi; Kurniawan, Dimas Dwi (Jurnal Pendidikan Indonesia Gemilang, 2023)
One of the problems faced in the world of education is the problem of learning that needs to involve students in the learning process. Teachers still need to implement the use of learning models fully, so the learning process is only teacher-centered, and learning does not involve active students. This research was conducted to determine the effect of applying the discovery learning model on students' learning outcomes on the protists concept using the quasi-experimental method. The results showed that the students' learning outcomes on the protists concept in the experimental class after applying the discovery learning model on the protists concept (= 43.2) is better than the control class (= 40.6). In can be concluded that the there is an effect of applying the discovery learning model on students' achievement on the protists concept.